Historical perspectives on the American economy : (Cambridge University Press, 1995)
The essays included here are the "best sellers" of American economic history, the articles and chapters that most frequently appear on the syllabi of American economic history courses. Introductions add context, provide critical questions about the arguments and evidence, indicate important subsequent works, and suggest additional readings. Also included are a glossary and an appendix that provide a clear, simple introduction to regression analysis, necessary for reading the increasingly technical "cliometric" articles in the field.